Comparison and agreement of the most frequently recommended equations for estimating glomerular filtration rate for the diagnosis of chronic kidney disease in a population of Lima, Peru - Cieza Zevallos, Javier Antonio (2021)
Objective: To determine the correlation and agreement between the most frequently used formulas estimate the glomerular filtration rate (GFR) and the measured Creatinine Clearance (CrCl), in a Peruvian population. Methods: Study of correlation and agreement in a population with different stages of renal function. 175 patients were included, grouped by CrCl: Group 1: higher than 140, Group 2: between 140 and 90, Group 3: Between 90 and 60, Group 4: less than 60 ml/min/1,73 m2 . Height and weight were measured to calculate body mass index (BMI). Obese patients (BMI>29) were excluded. Using a 24-hour urine collection and a serum creatinine sample, creatinine clearance was measured (normalized for 1.73 m2  of body surface). Formulas considered for analysis were: Cockroft and Gault,MDRD, CKD-EPI and a Peruvian formula proposed by Vásquez. Correlation was analyzed by Pearson coefficient between studied formulas and the measured CrCl; and its agreement was studied by Bland Altman analysis using the difference between the result obtained by each formula and the measured CrCl. Results: All studied formulas showed an acceptable degree of correlation but CKD-EPI formula had considerable imprecision. The formulas by Vásquez and MDRD showed slightly favorable differences in patients with CrCl<60 ml/min. Conclusion: We recommend the use of any of the studied formulas with exception of CKD-EPI in our population.